Alkylation of a hydrophilic photosensitizer enhances the contact-dependent photo-induced oxidation of phospholipid membranes. (March 2021) - Vignoni, Alejandro; Layana, Carla; Junqueira, Helena C.; Thomas, Andrés H.; Itri, Rosangela; Baptista, Mauricio S.; Vignoni, Mariana
Abstract: Lipophilic photosensitizers able to photo-induce lipid oxidation in biomembranes are, in general, much more efficient than hydrophilic ones; acting through the formation of singlet oxygen ( 1 O2 ), which oxidizes the fatty acid double bonds (type II mechanism). Here we investigate the binding and photosensitizing properties of 4-(decyloxy)pteridin-2-amine ( O -decyl-Ptr) using unilamellar vesicles of 1, 2-dioleoyl- sn -glycero-3-phosphocholine (DOPC), a phospholipid with monounsaturated fatty acids. By means of molecular dynamic (MD) simulations, we showed that O -decyl-Ptr binds to the membrane in a localization that favors the direct reaction of the triplet excited state of O -decyl-Ptr with DOPC double bonds. As a consequence, although 1 O2 is formed, O -decyl-Ptr acts mainly as a contact-dependent photosensitizer, meaning through radical formation (type I mechanism). Mass spectrometry analysis of vesicles irradiated in the presence of O -decyl-Ptr, demonstrated the generation of alcohols (LOH), ketones (LO) and hydroperoxides (LOOH). In agreement with the mechanistic hypothesis proposed, LOH and LO (type I photooxidation products) are formed faster than LOOH (type II photooxidation product). Interestingly, no short-chain oxidized products were detected. Accordingly, membrane fluctuations and formation of filaments and buds are observed during in-situ photo-activation of O -decyl-Ptr in giant unilamellar vesicles due to changes in membrane spontaneous curvature. Finally, we evaluated the effect of the photochemical processes studied at a cellular level and demonstrated in experiments of viability of mammalian cells that O -decyl-Ptr has important photodynamic properties. Similar experiments performed using the hydrophilic photosenstizer pterin (Ptr) show that alkylation leads to a striking increase in the efficiency of photosensitized lipid oxidation. Highlights: O -decyl-Ptr acts mainly as contact-dependent photosensitizer and not by 1O2 formation. O-decyl-Ptr binds to the membrane in a specific location, showed by MD simulations. O -decyl-Ptr photo-induces oxidation in DOPC vesicles, producing LOOH, LO and LOH. Cell viability is reduced by 50% when using O -decyl-Ptr as photosensitizer.